2015
DOI: 10.1177/2050640615612934
|View full text |Cite
|
Sign up to set email alerts
|

Gastric malt lymphoma: Analysis of a series of consecutive patients over 20 years

Abstract: Introduction and aims: Gastric mucosa-associated lymphoid tissue (MALT) lymphoma is closely associated with Helicobacter pylori (HP) infection. Our aim was to evaluate demographic, clinical and endoscopic characteristics of gastric MALT lymphoma patients, as well as to analyse response to treatment and factors that affect complete remission (CR) and relapse. We also assessed the long-term prognosis. Methods: The study involved a retrospective evaluation of consecutive patients admitted with gastric MALT lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 23 publications
4
39
1
Order By: Relevance
“…Among 16 patients diagnosed at stage EIV, nine achieved CR after chemotherapy ± surgery and 3 of 7 without remission died due to disease progression. The 5‐ and 10‐year overall disease free survival rates were 90.5% and 79.1%, respectively …”
Section: Gastric Mucosa‐associated Lymphoid Tissue (Malt) Lymphomamentioning
confidence: 98%
See 1 more Smart Citation
“…Among 16 patients diagnosed at stage EIV, nine achieved CR after chemotherapy ± surgery and 3 of 7 without remission died due to disease progression. The 5‐ and 10‐year overall disease free survival rates were 90.5% and 79.1%, respectively …”
Section: Gastric Mucosa‐associated Lymphoid Tissue (Malt) Lymphomamentioning
confidence: 98%
“…The 5and 10-year overall disease free survival rates were 90.5% and 79.1%, respectively. 8 In another retrospective study, the effectiveness of H. pylori eradication therapy was assessed in 345 Korean patients with GML, regardless of the H. pylori infection status or disease stage. H. pylori infection was detected in 317 of 345 patients (91.9%).…”
Section: Gastric Cancer: Biomarkers For Treatment Responsementioning
confidence: 99%
“…15 and 83% (78/94) in a Portuguese single-center retrospective study. 22 However, CR criteria varied among those studies. In a systematic review of 32 reports including those listed above, 23 CR was found to have been achieved in 77% (1091/1408).…”
Section: Safetymentioning
confidence: 99%
“…H. pylori are also implicated in the majority of cases of peptic ulcer disease, particularly duodenal ulcer. Eradication therapy is both effective in healing peptic ulcer disease and in preventing relapse, and is cost-effective (Moleiro et al, 2016).H. pylori infection has also been associated with weight loss and failure to thrive among older adults.…”
Section: Incidence Of H Pylorimentioning
confidence: 99%